STUDYING THE ASSOCIATION BETWEEN POSTGRADUATE TRAINEES' WORK HOURS, STRESS AND THE USE OF MALADAPTIVE COPING STRATEGIES - Kasi, Pashtoon Murtaza; Khawar, Talha; Khan, Farooq Hasan; Kiani, Jawad Ghazanfar; Khan, Umber Zaheer; Khan, Hadi Mohammad; Khuwaja, Urooj Bakht; Rahim, Musa (Journal of Ayub Medical College Abbottabad, 2007)
Background: The growing debate regarding long working hours of postgraduate trainees has been receiving considerable attention recently. This greater workload contributes to increasing stress. Our objective was to specifically study the association between long working hours, stress and the greater use of '˜maladaptive' coping strategies. Methods : A cross-sectional descriptive study was carried out on all interns and residents at the Aga Khan University Hospital during February to May, 2005. Level of stress was measured by use of General Health Questionnaire (GHQ-12) and the use of maladaptive coping mechanisms through Brief Cope-28. Results: 55.1 % scored over the threshold for mild stress i.e. GHQ > 3, while more than 46% of the trainees scored over the threshold of more than 4 for morbid stress. Trainees under stress reported more working hours on average as compared to those not under stress, 83.8 and 74.7 hours respectively. At the same time, those working for longer hours were more likely to have used these negative coping mechanisms, which would further contribute to more stress rather than relieving it. Conclusions: Significant levels of stress have been identified. Along with this, those working for longer hours were more likely to have used these negative coping mechanisms. Reduction of working hours is important. Simultaneously, interventions need to be planned at imparting knowledge, awareness and skills to cope with various kinds of stressors encountered by a trainee during his/her training. Additionally, limits need to be devised for the working hours of the trainees. Keywords: Postgraduate, resident, intern, working hours, stress, maladaptive coping strategies, GHQ-12, Brief Cope, Pakistan, Medical Education.